A CORRELATIONAL STUDY BETWEEN TEACHER’S INSTRUCTIONAL TIME AND STUDENTS' ENGLISH ACHIEVEMENT - Ramona Paputungan; Maru, Mister Gidion; Lambe, Livianni (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
Instructional time plays an important role in supporting students’ achievement, particularly in learning English as a foreign Language. This study aims to examine the relationship between teacher instructional time and students’ English achievement at SMP Negeri 4 Tondano. This research employed a quantitative method with a correlational design. The participants of this study consisted of one English teacher and ten eight-grade students’ in the 2024-2025 academic year. Data were collected through questionnaires to measure teacher instructional time and students’ perceptions, as well as students’ English achievement scores obtained from academic records. The data were analyzed using the Pearson Product-Moment Correlation through SPSS. The results showed that the significance value was 0.032, which is less than 0.05, and the Pearson correlation coefficient was 0.645. it shows that there is a strong positive correlation between teacher instructional time and students’ English achievement. This study concluded that there is significant positive correlation between well managed instruction time and students’ English achievement. It is important to note that this study only shows the correlation between the two variables, but it is not showing the cause and effect relationship.